Wnt Signaling Regulation of Tissue Architecture (EMT and MET) and Morphogenesis: Consequences for Colorectal and Liver Cancer - Fifis, T.; Tran, B.; Schwab, R.; Johanson, T.; Warner, N.; Barker, N.; Vincan, Elizabeth (Wiley Blackwell, 2014)
© 2014 John Wiley & Sons, Inc. The different branches of the Wnt signaling pathway were first characterized in developmental contexts, but in recent times, each branch has been implicated in tumor growth and progression. This chapter exemplifies this link between development and cancer by focusing on two Wnt-driven cancers, colorectal cancer (CRC) and hepatocellular carcinoma (HCC). It focuses on the processes of epithelial-to-mesenchymal transition (EMT) and the reverse transition, mesenchymal-to-epithelial transition (MET), both fundamental mechanisms of tumor metastasis and morphogenesis. HCC shares many parallels with CRC with respect to the involvement of Wnt signaling in cancer initiation and progression.